Self Censorship among Icelandic Journalists - Guðmundsson, Birgir (Stjórnsýslustofnun, 2015)
The discussion on media self-censorship has flourished in Iceland after the attacks on the Charlie Hebdo editorial offices in January 2015 and after some dramatic changes in the top management and owner-groups of some of the media firms. But what is this experience that journalists describe as self censorship? This paper attempts to answer two main research questions. On the one hand the question how journalists understand the concept of selfcensorship. On the other hand the question: what is the experience of Icelandic journalist of self-censorship? The approach is the one of a qualitative research and is based on interviews with six experienced journalists. The main findings suggest important influence of the social discourse on news and news values of journalists and their tendency for self-censorship. This discourse is partly directed by politicians and influential bloggers and also by a massive discussion by active social media users. Furthermore the findings suggest, that ownership and the location of the particular medium where a journalist works in the lineup of different commercial-political blocks in the media market, is important for self-censorship. Finally it seems that journalists understand the concept selfcensorship in a different manner and that it is important to define the term carefully if it is to be used as an analytical tool. Umræða um sjálfsritskoðun fjölmiðla hefur tekið kipp hér á landi eftir árásir á ritstjórnarskrifstofur Charie Hebdo í París í janúar 2015 og sviptingar í yfirstjórn og eigendahópi íslenskra fjölmiðla. En hver er sú reynsla sem blaðamenn lýsa sem sjálfsritskoðun og hvað merkir hugtakið? Í þessari könnun er leitað svara við tveimur rannsóknarspurningum. Annars vegar hvernig blaðamenn skilja hugtakið sjálfsritskoðun og hins vegar hver væri reynsla íslenskra blaðamanna af sjálfsritskoðun. Byggt var á fyrirbærafræðilegri aðferð með viðtölum við sex reynda blaðamenn. Megin niðurstaðan er sú að áhrif umræðunnar um fréttir og fréttamat blaðamanna hafi mikil áhrif á efnistök ...